NADPH oxidase 4 inhibition is a complementary therapeutic strategy for spinal muscular atrophy - El Khoury, Mirella; Biondi, Olivier; Bruneteau, Gaelle; Sapaly, Delphine; Bendris, Sabrina; Bezier, Cynthia; Clerc, Zoé; Akar, Elias Abi; Weill, Laure; Eid, Assaad A.; Charbonnier, Frédéric (Frontiers in Cellular Neuroscience, 2023)
Introduction Spinal muscular atrophy (SMA) is a fatal neurodegenerative disorder, characterized by motor neuron (MN) degeneration and severe muscular atrophy and caused by Survival of Motor Neuron (SMN) depletion. Therapies aimed at increasing SMN in patients have proven their efficiency in alleviating SMA symptoms but not for all patients. Thus, combinational therapies are warranted. Here, we investigated the involvement of NADPH oxidase 4 (NOX4) in SMA-induced spinal MN death and if the modulation of Nox4 activity could be beneficial for SMA patients. Methods We analysed in the spinal cord of severe type SMA-like mice before and at the disease onset, the level of oxidative stress and Nox4 expression. Then, we tested the effect of Nox4 inhibition by GKT137831/Setanaxib, a drug presently in clinical development, by intrathecal injection on MN survival and motor behaviour. Finally, we tested if GKT137831/Setanaxib could act synergistically with FDA-validated SMN-upregulating treatment (nusinersen). Results We show that NOX4 is overexpressed in SMA and its inhibition by GKT137831/Setanaxib protected spinal MN from SMA-induced degeneration. These improvements were associated with a significant increase in lifespan and motor behaviour of the mice. At the molecular level, GKT137831 activated the pro-survival AKT/CREB signaling pathway, leading to an increase in SMN expression in SMA MNs. Most importantly, we found that the per os administration of GKT137831 acted synergistically with a FDA-validated SMN-upregulating treatment. Conclusion The pharmacological inhibition of NOX4 by GKT137831/Setanaxib is neuroprotector and could represent a complementary therapeutic strategy to fight against SMA.